Studio talks – the city as a lab (Revista Apotheke, 2025)
The article investigates the artist’s studio as an expanded and fluid device that transcends the physical space and manifests itself in the artist’s displacements, attention, and presence in their surroundings. The city, on the other hand, acts not only as a background but as an active agent in their professional training and creative process. Conversely, in counterpoint to the urban rhythm, the studios are configured as spaces for the suspension of time, in which poetic experience matters more than the material result of the work. The authors reflect on the challenges of producing art in contexts of relatively scarce economy, articulating their academic trajectories and personal affinities. The text, written in the third person, seeks the horizontality and fluidity of the narrative, proposing a critical review of the myth of the isolated artist in their atelier. By understanding this space as a territory for experimentation and an extension of everyday life, the article highlights the permeability between the city, the body, and creation, where every lived experience becomes the visual and sensible material of the artistic practice.
Keywords: visual arts; city; painting; poetic experience; creative process